Coagulopathy in Patients of Chronic Liver Disease Admitted in Sir Ganga Ram Hospital (SGRH) - N. M. ANWAR, F. M. CHEEMA, S. WASEEM, H, S. S. BUKHAR (Journal of Fatima Jinnah Medical University, 2018)
Background: In patients of chronic liver disease, the blood profile may derange due to abnormal functioning of liver. But the evidence was missing from local population. Objective: To determine the coagulation abnormality of patients presenting with chronic liver disease and its relation with outcome of patient. Material & Methods: This cross sectional study was conducted on 50 patients, previously diagnosed cases of CLD. All patients underwent laboratory examination by taking venous blood sample. Patients blood samples were tested for coagulation abnormalities including prothrombin time (PT), activated partial thromboplastin time (aPTT) and platelet count. Results: According to the study, mean age of the patients was 52.08±10.07years. There were 23 (46%) males while 27 (54%) were females. The mean weight of patients was 63.88±7.43kg. (Table#1) Thirty-four patients had mildly prolonged PT, 31 patients had mildly prolonged aPTT. Thus, 35 patients had prolonged clotting profile. In this study, 12 patients had platelet count between 50,000-100,000/mm3 while 5 patients had <50,000/mm3. Conclusion: Coagulation abnormalities were intense in CLD patients. Most of the patients showed deranged coagulation profile and decreased platelet count.